Bifidobacterium animalis subsp. lactis Bi‐07 contributes to increasing lactose digestion: evaluation of a health claim pursuant to Article 13(5) of Regulation (EC) No 1924/2006. (29th July 2020) - ,; Turck, Dominique; Castenmiller, Jacqueline; De Henauw, Stefaan; Hirsch‐Ernst, Karen Ildico; Kearney, John; Knutsen, Helle Katrine; Maciuk, Alexandre; Mangelsdorf, Inge; McArdle, Harry J; Naska, Androniki; Pelaez, Carmen; et al.
Abstract: Following an application from DuPont Nutrition Biosciences ApS submitted for authorisation of a health claim pursuant to Article 13(5) of Regulation (EC) No 1924/2006 via the Competent Authority of Ireland, the EFSA Panel on Nutrition, Novel Foods and Food Allergens (NDA) was asked to deliver an opinion on the scientific substantiation of a health claim related to Bifidobacterium animalis subsp. lactis Bi‐07 (Bi‐07) and contribution to increasing lactose digestion. The scope of the application was proposed to fall under a health claim based on newly developed scientific evidence. The food proposed by the applicant as the subject of the health claim is Bi‐07. The Panel considers that Bi‐07 is sufficiently characterised. The claimed effect proposed by the applicant is 'improvement of lactose digestion'. The Panel considers that increasing lactose digestion is a beneficial physiological effect for individuals with lactose maldigestion provided that the symptoms of lactose maldigestion are improved. Two human intervention studies which investigated a single dose effect of Bi‐07 on lactose digestion using the hydrogen breath test, as well as on gastrointestinal symptoms were submitted. These studies show that consumption of Bi‐07 (10 12 CFU) increases lactose digestion in individuals with lactose maldigestion and that Bi‐07 exhibits lactase activity in vitro . However, these studies provide no evidence that increasing lactose digestion through the consumption of Bi‐07 (10 12 CFU) improves gastrointestinal symptoms of lactose maldigestion, which is considered a beneficial physiological effect. The Panel concludes that a cause and effect relationship has not been established between the consumption of Bifidobacterium animalis subsp. lactis Bi‐07 and a beneficial physiological effect (i.e. the improvement of symptoms of lactose maldigestion) in individuals with lactose maldigestion.